1964
DOI: 10.1063/1.1726132
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Emission Spectrum of NO

Abstract: The emission spectrum of the vibration—rotation bands of the electronic ground state of nitric oxide has been observed in the 1.83–1.95- and 2.63–2.81-μ regions under moderately high resolution. The source of the spectrum was a high-tension discharge maintained through streaming nitric oxide gas at pressures of less than 1 atm. A detailed analysis of the 2–0, 3–;1, and 4–;2 bands, occurring at 2.69, 2.73, and 2.77 μ, respectively, has been carried out. Accurate values obtained for many of the rotational and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

1965
1965
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Nitric oxide plays an important role in the physiology of living organism; therefore, it was investigated intensively. A number of quantum mechanical calculation showed that the high precision CCSD­(T) method gives interatomic distance d N–O CCSD(T) = 1.169 Å in good agreement with the experimental value d N–O exp = 1.151 Å. , Our DFT calculations give d N–O DFT = 1.191 Å which is also in reasonably good agreement with the experiment. The NO dissociation energy experimental value is Δ E diss exp (NO) = 6.515 eV .…”
Section: Methodssupporting
confidence: 81%
“…Nitric oxide plays an important role in the physiology of living organism; therefore, it was investigated intensively. A number of quantum mechanical calculation showed that the high precision CCSD­(T) method gives interatomic distance d N–O CCSD(T) = 1.169 Å in good agreement with the experimental value d N–O exp = 1.151 Å. , Our DFT calculations give d N–O DFT = 1.191 Å which is also in reasonably good agreement with the experiment. The NO dissociation energy experimental value is Δ E diss exp (NO) = 6.515 eV .…”
Section: Methodssupporting
confidence: 81%
“…(1) N + 0 2 -NO + 0 All of thesv, reactions are exothermic. Reactions (2), (3), (4), (5) and (6) are known to be at least visibly chemiluminescent, and all except (8) and (11) are expected to be chemiluminescent in the infrared.…”
mentioning
confidence: 99%
“…In conjunction with the studies on infrared chemiluminescence, a study was made of the emission spectrum of several gases which had been activated by a radio-frequency discharge. The spectra of methane, ethane and ketene were obtained [4], The infrared emission of nitric oxide was studied as a function of cell pressure, Horn and Dickey [ 5] reported on such a study at pressures of 200 torr, Wilkinson, Price, and Mould [6]have also studied such emissions at relatively high pressures.…”
mentioning
confidence: 99%
See 1 more Smart Citation